The three faces of takotsubo cardiomyopathy in a single patient. Issue 1 (16th December 2019) - Janus, Scott E.; Hoit, Brian D.
Abstract: While the classical apical ballooning takotsubo cardiomyopathy (TC) was first reported in the 1990s, the rarer mid‐ventricular and basal variants were not formally recognized until recently and they remain poorly understood. In this case report, we describe a 67‐year‐old woman who, during her hospitalization for a subarachnoid hemorrhage and subsequent readmission, experienced multiple complications, each of which resulted in a different variant of TC. To our knowledge, this is the first report of a single patient developing all three variants of TC.